Pengenalan Senam Lansia untuk Pencegahan Stroke pada Warga Lansia Sumber RW 16 Surakarta Jawa Tengah - Muhammad Farkhan Al-Hafidz; Wahyuni Wahyuni; Seliana Debi (Universitas 45 Surabaya, 2024)
Elderly people suffer deterioration in body function that can cause bodily disorders primarily in the brain and may cause strokes. The 2018 data for basic health research explains that the above 75 years of age are the largest scarring of all stroke patients diagnosed by medical personnel and the lowest in age 15-24. Other ailments that can cause strokes are hypertension, heart disease, diabetes mellitus and obesity. Physiotherapy is one of the best nonpharmacological efforts to treat stroke patients and to improve the quality of life of older people such as maintenance, restoration, and restoration of limb. The promotive and preventive effort of people living in villages, source rw 16 surakarta, has been established as part of the preliminary screening of strokes, followed by the correction of strokes, calisthenics and recent evaluations of the post test to assess the knowledge of strokes and the resulting increased knowledge of participants.